Surveillance of antimicrobial resistance in recent clinical isolates of Gram-negative anaerobic bacteria in a Greek University Hospital. (April 2020) - Maraki, Sofia; Mavromanolaki, Viktoria Eirini; Stafylaki, Dimitra; Kasimati, Anna
Abstract: The aim of our study was to determine the antimicrobial susceptibility profiles of 267 Gram-negative clinically significant anaerobes, isolated between October 2016 and October 2019, in a Greek university hospital. The species identification was performed by conventional methods and using the Vitek 2 automated system. Antimicrobial susceptibility testing to determine the MICs was performed by the E-test method. The antimicrobial agents tested were penicillin, ampicillin, amoxicillin-clavulanic acid, piperacillin-tazobactam, cefoxitin, imipenem, meropenem, clindamycin, metronidazole, moxifloxacin, chloramphenicol and tigecycline. The results were interpreted using the CLSI and FDA breakpoints. The majority of the isolates belonged to Bacteroides fragilis group (58.8%), followed by Prevotella spp. (23.2%), Fusobacterium spp. (11.2%) and Veillonella spp. (6.4%). The most prevalent types of infection were skin and soft tissue infections (34.8%), and inta-abdomonal infections (29.6%). Among all isolates tested, the lowest rates of resistance (<5%) were detected to carbapenems, metronidazole, chloramphenicol and tigecycline. Resistance to piperacillin-tazobactam was observed in 5.4%, 24.6%, 3.3% and 17.6%, of B. fragilis, B. fragilis group, Fusobacterium spp. and Veillonella spp. isolates, respectively. Although a high prevalence of resistance to clindamycin, cefoxitin, and moxifloxacin, was detected particularly among members of the B. fragilis group, cefoxitin resistance was low for Prevotella spp. (3.2%), Fusobacterium spp. (3.3%) and Veillonella spp. (0%). Our findings underscore the need for periodic monitoring of antimicrobial resistance in order to guide empirical therapy. Highlights: Bacteroides species were the most commonly isolated Gram-negative anaerobes. The most prevalent types of infection were skin and soft tissue infections. Resistance to carbapenems, metronidazole, chloramphenicol and tigecycline was low. Bacteroides spp exhibited the highest resistance rates to clindamycin and cefoxitin. Multidrug resistance was detected among 16.6% of Bacteroides spp. isolates.